IKLAN PERAWATAN KULIT WAJAH DI KORAN BINTANG BORNEO PADA TAHUN 1930 - Fadilah, Yesi Nur (Langgong: Jurnal Ilmu Sosial dan Humaniora, 2023)
Newspapers existed as a medium for information and news during the Dutch colonial period. The information and news contained in advertisements is not only about socio-political economics but also advertising. Cosmetic advertisements were the ones that appeared most often in newspapers in the 1930s. The development of skin care products has changed women's perspective on beauty. Cosmetic advertisements in the 1930s outlined the trend and taste of beauty by having clean, brownish skin. This research aims to determine how skin care advertisements in the Bintang Borneo newspaper reflect beauty trends and preferences in 1930.